2013
DOI: 10.4028/www.scientific.net/msf.753.321
|View full text |Cite
|
Sign up to set email alerts
|

Strain Induced Abnormal Grain Growth in Nickel Base Superalloys

Abstract: Under certain circumstances abnormal grain growth occurs in Nickel base superalloys during thermomechanical forming. Second phase particles are involved in the phenomenon, since they obviously do not hinder the motion of some boundaries, but the key parameter is here the stored energy difference between adjacent grains. It induces an additional driving force for grain boundary migration that may be large enough to overcome the Zener pinning pressure. In addition, the abnormal grains have a high density of twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…As seen here, initial strain bears a definite and significant influence on not only the emergence rate for AGG, but also, by extension, the continued progression rate. These findings are supported by the work of Decker et al [32], He et al [33][34][35], and Cho et al [36], who all showed that among instances of self-similar AGG, initial strain content can serve as a significant driving force for grain boundary migration among low-energy, high-mobility grain boundaries [9,36,37]. In this work, this driving force is incorporated into the predictive estimate for AGG advancement as a superposition of a nominal rate (where ε = 0) combined with a weighted contribution from the additional plastic strain present.…”
Section: Discussionsupporting
confidence: 77%
“…As seen here, initial strain bears a definite and significant influence on not only the emergence rate for AGG, but also, by extension, the continued progression rate. These findings are supported by the work of Decker et al [32], He et al [33][34][35], and Cho et al [36], who all showed that among instances of self-similar AGG, initial strain content can serve as a significant driving force for grain boundary migration among low-energy, high-mobility grain boundaries [9,36,37]. In this work, this driving force is incorporated into the predictive estimate for AGG advancement as a superposition of a nominal rate (where ε = 0) combined with a weighted contribution from the additional plastic strain present.…”
Section: Discussionsupporting
confidence: 77%
“…Bozzolo et al showed that in low strain torsion tests Alloy 718 produced abnormally large grains that grew unhindered despite the presence of δ phase particles [5]. The large grains seen in this study had roughly twice the amount of twin boundaries than normalsized grains, appearing scattered throughout a low strained part of the microstructure.…”
Section: Introductionsupporting
confidence: 49%
“…Samples of the alloy came from regions of low strain during forging. Simulations and previous studies [5,6] suggest that the critical strain for abnormal grain coarsening during solution heat treatment is less than 0.2. However initial tests on this material have produced negative results.…”
Section: Discussionmentioning
confidence: 62%
“…3. A fully recrystallized microstructure was observed [17]. Table 2 illustrates the evolution of average grain size after compression of samples deformed at 980°C and 1020°C.…”
Section: Resultsmentioning
confidence: 95%